Graduate qualities and selection criteria in Malaysian financial institutions - Abdul Adzis, Azira; Kadir @ Shahar, Hanita; Abu Bakar, Ab Malek Foad (Universiti Utara Malaysia, 2006)
The issue of unemployed graduates in Malaysia has triggered a widely concern not only to the government but also to the higher education institutions and employers.In response to this issue, this research attempts to investigate what are the criteria that financial institutions in Malaysia actually seek from graduates to fill job vacancies in their organisation, and what are the shortcomings that they usually find in local university graduates particularly Universiti Utara Malaysia (UUM) graduates.A total of 167 questionnaires have been sent to the human resource manager of each financial institution.The results show that the foremost criterion that financial institutions seek from graduates is pleasant appearance, followed by good CGPA and lastly relevant experience.This research also attempts to identify major skills needed from graduate to be the respondents’ employee.The findings highlight that good communication skills in English, interpersonal skills, teamwork skills, critical thinking skills, and English writing skills are indeed the essential skills needed from graduates.This research finding also discovered that the main weaknesses of UUM graduates are poor in English communication skills and English writing skills.